Synthesis of forsterite with high strength and low acid solubility using magnesite tailings. Issue 8 (15th April 2023) - Dong, Haoran; Liang, Yonghe; Nie, Jianhua; Cai, Manfei; Ju, Maoqi; Li, Zhou; Wen, Lidong; Zhou, Yaofei
Abstract: The synthesis of forsterite from magnesite tailings is beneficial to the secondary resource utilization of tailings and maintaining ecological balance. And the synthetic forsterite multiphase material can be used as the raw material of ceramic proppants instead of natural forsterite ore. In this study, forsterite multiphase material was synthesized via a solid-state reaction method using magnesite tailings and silica. Furthermore, the phase composition, microstructure, apparent porosity, bulk density, mechanical properties, and acid solubility of the synthetic material were characterized. The results show that the densification and forsterite phase content of the synthetic forsterite multiphase material gradually increase as silica is added. Additionally, the excess silica generates enstatite and quartz phases, which increase the glass phase in the material and decrease the forsterite phase. Forsterite multiphase material with optimal mechanical properties was synthesized from 83 wt% magnesite tailings and 17 wt% silica. The acid solubility of the synthetic forsterite multiphase material was as low as 4.33%.